Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1017/s1368980012005071
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an FFQ to assess short-term antioxidant intake against 30 d food records and plasma biomarkers

Abstract: Objective: To validate a brief FFQ developed for capturing short-term antioxidant intake in a sample of US college students. Design: A seventy-four-item antioxidant FFQ was developed based on major antioxidant sources in the American diet. The FFQ was validated against 30 d food records (FR) and plasma antioxidant concentrations. The reliability of the FFQ was evaluated by two FFQ administered at a 1-month interval. Settings: University of Connecticut, CT, USA. Subjects: Sixty healthy college students. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Published data suggest that mean α-tocopherol intakes in adults in some European countries (Finland, Sweden) (Amcoff et al, 2012;Helldán et al, 2013) are higher than those observed in the USA, where γ-tocopherol intakes are generally reported to be higher than in the EU (Gao et al, 2004;Maras et al, 2004;Dixon et al, 2006;Mahabir et al, 2008;Signorello et al, 2010;Yang et al, 2014a;Yang et al, 2014b).…”
Section: Dietary Intakementioning
confidence: 99%
“…Published data suggest that mean α-tocopherol intakes in adults in some European countries (Finland, Sweden) (Amcoff et al, 2012;Helldán et al, 2013) are higher than those observed in the USA, where γ-tocopherol intakes are generally reported to be higher than in the EU (Gao et al, 2004;Maras et al, 2004;Dixon et al, 2006;Mahabir et al, 2008;Signorello et al, 2010;Yang et al, 2014a;Yang et al, 2014b).…”
Section: Dietary Intakementioning
confidence: 99%
“…The self-administered FFQ is the primary method of dietary assessment used in epidemiological studies ( 11 ) , owing to its capability of capturing a long-term dietary behaviour, low participant burden and ease in data processing. A new FFQ was developed to assess a comprehensive antioxidant intake profile containing vitamin C, vitamin E, carotenoids, flavonoids and proanthocyanidins, as well as total antioxidant capacity (TAC), an integrated measure of the ‘quenching abilities’ of antioxidants ( 12 ) . This FFQ provided a reasonable validity in a sample of American college students ( 12 ) .…”
mentioning
confidence: 99%
“…Table 2 shows the dietary intake of provitamin A carotenoids compiled from the literature [ 16 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Data are listed by geographical origin and by the subpopulations studied in the original articles when reported by age or sex.…”
Section: Resultsmentioning
confidence: 99%